Borders - identities - home: Theory-based approaches to constructs and concepts in a cross-border context - Antje Schönwald; Annette Spellerberg; Florian Weber (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
Life in the border regions within the European Union has become normal for many people, especially for younger generations. Crossing the borders is part of everyday life. In recent years, until the refugee crisis, national borders had lost significance due to their increased permeability, although neither borders nor border demarcations have ever become meaningless. National policies and frameworks determine fundamental orientations that have specific implications on both sides of borders. This is associated with processes of inclusion and exclusion, (regional) identities, feelings of belonging and issues concerning a sense of home. Against this background, this paper provides a theory-based introduction to the central constructs and concepts that gain significance in the cross-border context: border(s) and border demarcations, (spatial and regional) identities and home. Identification processes are illuminated and categorised using the example of the Greater Region.
urn:nbn:de:0156-40970927; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Cross-border context; theory; identities; home; Greater Region